Challenges and ownership issues facing by low (B40) and medium income group (M40) in Selangor - Mohamed Osman, Mariana; Zainudin, Farah Eleena; Rabe, Noor Suzilawati; Hitam, Mizan; Ponrahono, Zakiah (Malaysian Institute of Planners, 2020)
A shelter is a necessity based on Maslow’s hierarchy of needs and in the present situation, owning a home is quite difficult for low-income earners living in urban area. Currently, it was found that people living in a city mostly prefer to rent rather thanbuying a house due to the expensive house prices. Access to decent and affordable housing can be consider as fundamental human right and the government have the responsibility to address this human right issue. Thus, the study tries to analyse the perception of community specifically within the B40 and M40 living in Selangor towards the idea of purchasing a house. The study surveyed 500 respondents using stratified random sampling. The study found that the main challenges was the high prices of property, followed by unable to obtained loan and high monlty expenses that lead to them unable to pay for the 10% deposit of the house. In term of affordability level, with level 3 considered as afforabable range, the study found that Petaling and Kuala Langat were severely unaffordable followed by Hulu Langat, Klang, Sepang and Sabak Bernam (Seriously unaffordable) and Hulu Selangor, Kuala Selangor and Gombak were at moderately unaffordable.